Laterality related to the successive selection of Dutch national youth soccer players. Issue 22 (17th November 2017) - Verbeek, Jan; Elferink-Gemser, Marije T.; Jonker, Laura; Huijgen, Barbara C. H.; Visscher, Chris
ABSTRACT: In the general population, estimates of left-foot preference are around 20%. In soccer, specific tasks create positional demands, requiring 40% of the players to be left-footed. Whether and how this is related to the selection of players is unknown. To examine the successive selection of soccer players for Dutch national youth teams in relation to foot preference, 280 youth players (age = 16.2 ± 1.08 years) were monitored from the U16 through the U19 teams over the last 5 years. No difference in successive selection between left- and right-footed players was found ( p < 0.05). Regardless of foot preference, more than 50% of the selected players were deselected out of a national youth team after 2 years. On average, 31% of the national youth players were left-footed, which is higher than expected, based on population estimates (χ 2 (1) = 37.49, p < 0.001, w = 0.27). However, there was an under-representation of left-footed players, based on expected positional demands (i.e., attack, midfield, defence) ( χ 2 (1) = 16.83, p < 0.001, w = 0.18). The conclusion is that left-foot preference increases the probability of selection in Dutch national youth soccer teams.